Pengaruh Job Insecurity Dan Komitmen Organisasi Terhadap Turnover Intention Karyawan Pada PT Hilon Sumatera - Delvina Siregar, Viona; Mardhiyah, Ainun; Marakali Siregar, Onan (PENG: Jurnal Ekonomi dan Manajemen, 2025)
Employees are important assets in achieving success, enabling a company to compete and reach its goals. Therefore, companies strive to address employee needs as much as possible to avoid employee turnover. However, this phenomenon remains unavoidable over time, due to various factors. For instance, turnover can be triggered by employees' feelings of insecurity regarding their careers and a lack of commitment to carrying out the company’s mission. The aim of this study is to analyze the relationship between Job Insecurity and Organizational Commitment with Turnover Intention at PT Hilon Sumatera. This study also seeks to examine the effect of Job Insecurity and Organizational Commitment on employee turnover in the company. The research was conducted using a quantitative method with an associative approach. Data were collected by distributing questionnaires to 97 employees using a purposive sampling technique, supported by secondary data such as various books and previous research. The data were analyzed using instrument tests, classical assumption tests, multiple linear regression, and hypothesis testing as tools for data interpretation. The results of the study show that Job Insecurity and Organizational Commitment have a significant influence on changes in Turnover Intention, with correlation levels of 80.2% and 63.5%, respectively. The higher the job insecurity experienced by employees, the higher the turnover intention of employees, The higher the organizational commitment of employees, the lower the turnover intention of employees. Conversely, the lower the organizational commitment of employees, the higher the turnover intention of employees. Job Insecurity and Organizational Commitment have a significant influence on Turnover Intention among employees at PT Hilon Sumatera. Employee turnover can be reduced by minimizing or even eliminating employees' feelings of insecurity at work and by enhancing their organizational commitment.